A Bibliometric Analysis of Exchange Rate Fluctuations - Loso Judijanto; Khairul Nur Adli (West Science Interdisciplinary Studies, 2026)
The present paper applies bibliometric analysis to the research dedicated to fluctuations of exchange rates with the purpose to investigate the intellectual structure, thematic development, and international collaborative trends of the field. On the basis of Scopus indexed papers and with the help of visualization software (VOSviewer), it performs keyword co-occurrence, citation, co-authorship and country-level collaborations analysis. The results prove that the field is characterized by predominance of macro-financial issues, namely exchange rates, financial markets, volatility, and monetary policy, gradually embracing forecasting, risk management, and econometrics. The analysis of overlay and density confirms the tendency towards the transition from traditional macroeconomic interpretations of the phenomenon to forecasting and computational approaches. The analysis of citations suggests the multidisciplinary nature of the knowledge base, as it includes not only economics and finance, but also environmental and complex system studies. Finally, the network analysis reveals the prevalence of the US and China as global research centers, as well as the secondary importance of Europe and participation of emerging economies.